2012
DOI: 10.3109/00016357.2011.654249
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality-of-life in patients to be treated with fixed or removable partial dental prostheses

Abstract: The difference in OHRQoL between participants about to receive RDP and FDP was limited. The most frequently reported problems concerned functional limitations, discomfort and physical disabilities. Social handicap was not frequently reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
1
21
2
Order By: Relevance
“…The higher the score, the worse the patient finds his/her OHRQoL (range 0‐196). If an item had score 3 or 4, it was considered problematic and the frequency of problematic items was calculated …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the score, the worse the patient finds his/her OHRQoL (range 0‐196). If an item had score 3 or 4, it was considered problematic and the frequency of problematic items was calculated …”
Section: Methodsmentioning
confidence: 99%
“…From the OHIP‐49, a masticatory evaluation was also found, the OHIP‐Mas. It was found as the sum of the four masticatory items (Q1 + Q28 + Q29 + Q32) . The higher the OHIP‐Mas score, the more functional impairment judged by the patient (range 0‐16).…”
Section: Methodsmentioning
confidence: 99%
“…This aspect comes from the suggestion that users of dental prostheses have been through bad experiences related to oral health conditions, which may have had physical, social, and psychological impacts, making these individuals more sensitive to the perception of the oral health impacts on their quality of life (Özhayat and Gotfredsen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among the methodologies previously proposed for the OHIP are those that consider the sum of the responses of each item (Özhayat and Gotfredsen, 2013), the mean scores for each subscale (Pires et al, 2006), or even the percentage of reported oral The specific items for complete denture users (17, 18, and 30) were not considered in the analyses. n, sample size; λ, factor weights range (min-max); CFI, comparative fit index; GFI, goodness of fit; RMSEA, root mean square error of approximation; BIC, Bayes information criterion; AIC, Akaike information criterion; BCC, Browne-Cudeck criterion; AVE, convergent validity; CR, composite reliability; α, internal consistency; r 2 , squared correlation coefficient; OHIP, Oral Health Impact Profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation